P04 A retrospective multicenter analysis of the DERIVO® 2 Embolization Device in the treatment of ruptured and unruptured intracranial aneurysms. (29th August 2022) - Thormann, M; Sillis, N; Altenbernd, J; Berger, B; Cioltan, A; Loehr, C; Siebert, E; Bohner, G; Nordmeyer, H; Mpotsaris, A; Behme, D
Abstract : Introduction: Flow diverters have emerged as an effective and widely utilized therapy option for intracranial aneurysms. The DERIVO 2 Embolization Device (DED2) is a new addition to the market and promises better radiopacity. 1 Aim of study: The purpose of this study was to evaluate the safety and efficacy of the DED2. Methods: We conducted a retrospective multicenter analysis at six interventional facilities. Patients with unruptured or ruptured intracranial aneurysms were included. The primary objective was angiographic aneurysm occlusion at 6 months as measured by the OKM grading scale. Clinical outcome according to mRS was evaluated at 6 months, with major morbidity defined as mRS 3–5. Results: We included 37 patients treated with the DED2 between August 2020 and July 2021. Five patients had ruptured aneurysms. 27 patients were female, 10 male, with a medium age of 60. The median mRS was 0 (range 0–4). Average aneurysm size was 9.1 (7.9) mm, while average neck size was 6.8 (6.3) mm. In all cases the DED2 opened upon deployment. Thirty patients were eligible for clinical follow-up (81.1%). 25 (83.3%) had an mRS of 0 or 1, with no clinical deterioration in patients with pre-existing significant morbidity. Three patients died during the follow-up period, two of whom had ruptured aneurysms initially. Follow-up imaging was available in 27 patients (90%), with 23 (85.2%) demonstrating satisfactory aneurysm occlusion OKM grade C-D. Conclusion: The DED2 is both safe and effective in the treatment of ruptured and unruptured intracranial aneurysms. References: Fujimura S, Brehm A, Takao H, et al . Hemodynamic Characteristics and Clinical Outcome for Intracranial Aneurysms Treated with the Derivo Embolization Device, a Novel Second-generation Flow Diverter. World Neurosurg . 2021 Dec 17; Do you have any conflict of interest to declare? : No